Relation Between Unconjugated Bilirubin and Peripheral Biomarkers of Inflammation Derived From Complete Blood Counts in Patients With Acute Stage of Schizophrenia - Xu, Haiting; Wei, Yanyan; Zheng, Lina; Zhang, Hua; Luo, Tangren; Li, Hongjuan; Ma, Jinbao; Chen, Jingxu (Frontiers in Psychiatry, 2022)
Background Inflammation and oxidative stress are the major leading hypothetical causes of schizophrenia. Unconjugated bilirubin (UCB) is an efficient endogenous plasma antioxidant. Inflammation is closely linked to oxidative stress. The relationship between UCB and inflammatory markers should be paid close attention in schizophrenia acute stage. In this paper, combined UCB and inflammatory markers were evaluated for their capability in predicting schizophrenia in the acute stage to find an easy and effective indicator to identify acute schizophrenia. Methods A total of 6,937 acute schizophrenia patients and 6,404 healthy controls (HCs) were enrolled. UCB and peripheral biomarkers of inflammation derived from complete blood counts (CBC) were investigated in the subjects with acute schizophrenia, and the results were compared with HCs. Simultaneously, Spearman test was employed to assess the correlation between the variables, while logistic regression was adopted to determine the combined equation and receiver operating characteristic curve was used to evaluate the combined value of UCB and peripheral biomarkers of inflammation derived from CBC to predict schizophrenia in the acute stage. Results The study indicates that white blood cells, neutrophil, monocyte, mean platelet volume (MPV), red cell distribution width (RDW), neutrophil/lymphocyte ratio (NLR), and monocyte/lymphocyte ratio (MLR) have significantly increased in schizophrenia (p < 0.05 for all), while platelet, lymphocyte, and platelet/lymphocyte ratio (PLR) in schizophrenia have significantly decreased (p < 0.05 for all). UCB exhibits negative correlation with MPV significantly (r = 0.121, p < 0.001), and no correlation with neutrophil and monocyte. The correlations between UCB and other peripheral biomarkers of inflammation derived from CBC are very weak. MPV, RDW, NLR, MLR, PLR, and UCB were taken as independent variables for a logistic regression analysis. The model was as follows: Logit (P1)=-6.141+0.827 MPV+5.613 MLR-0.005 PLR-0.346 UBC. The combination demonstrates better effectiveness in predicting schizophrenia in the acute stage (AUC 0.831, 95% CI 0.825 to 0.837). Conclusion UCB has a protective effect on acute stage of schizophrenia, which is weak and indirect by affecting the proinflammatory processes. Our findings suggest that a combination of MLR, MPV, PLR, and UBC could be used to predict acute stage of schizophrenia.